Effects of double aging on inconel 718 fabricated by laser metal deposition - Tham, Nataniel Yong Syn (Nanyang Technological University, 2021)
Inconel 718 fabricated using Laser Metal Deposition has been found in recent years to be a viable option to fabricate or repair components. The metal possesses superior mechanical properties even at high temperatures, making it popular for applications particularly in the aerospace industry. Additionally, this process has lower heat affected zone allowing agile and localised repair compared to traditional welding or casting which has its disadvantages. Parts that are fabricated without any form of heat treatment are typically insufficient to meet application requirements. Hence, heat treatment is required in many situations to recover the mechanical properties and make it comparable to the traditional manufacturing methods. This paper focuses on the effects of double aging, one of the key stages in the heat treatment of Inconel 718. Various parameters involving number of aging stages, duration and temperature were referenced from both standards and literature. Studying the effects would involve characterisation techniques such as Optical Microscopy, Scanning Electron Microscopy, Field Emission Scanning Electron Microscopy and Transmission Electron Microscopy along with measuring the Hardness Values and performing tensile testing with fractography. Prior to testing, the samples were fabricated followed by heat treatment with different parameters. Across the various samples and parameters, there were noticeable findings providing clues into how the different phases form and affect the hardness. Firstly, it was found that only delta phases were present when the samples were directly aged at 850 °C for 4 hours, resulting in low strength and high elongation. Due to the high temperature, strengthening precipitates were unable to form and the Nb in the matrix caused an abundance of delta precipitates. Next, it was also found that by performing single aging at 760 °C, the hardness value decreased compared to the samples that were double aged. This is due to the coarsening effect of the γ′′, which increases the size of the precipitates in addition to making them coherent with the matrix. The hardness of the sample subjected to double aging with the sample aged at 760 °C followed by 650 °C for 10 hours was found to be higher than the sample single aged at 760 °C for 10 hours, implying a positive effect when aging at lower temperature. Single aging at 650 °C however, did not decrease the hardness values and additionally was found to have similar mechanical properties with solutionised samples that were double aged.